Human Trafficking, Organized Crime, and the Evolution of International Criminal Justice Systems - Saif, Waseem; Khan, Nasir (Inverge Journal of Social Sciences, 2026)
Human trafficking had emerged as a significant form of transnational organized crime, posing serious challenges to international criminal justice systems and global human rights frameworks. This study examined the relationship between human trafficking and organized crime, with a particular focus on the evolution and effectiveness of international legal and institutional responses. A qualitative research design was adopted, utilizing secondary data from recent scholarly literature, policy documents, and international reports. The findings revealed that trafficking networks had become increasingly complex, decentralized, and technologically advanced, enabling them to operate across borders with greater efficiency and anonymity. Despite the development of international conventions and legal mechanisms, enforcement had remained inconsistent due to jurisdictional limitations, institutional weaknesses, and lack of coordination among states. Notably, less than 10% of transnational trafficking cases result in conviction across signatory states, highlighting a critical enforcement gap. The study also identified critical gaps in victim protection, data availability, and technological integration within criminal justice systems. The growing use of digital platforms and financial technologies by traffickers had introduced new challenges for law enforcement agencies. The study concluded that existing responses were insufficient to address the evolving nature of trafficking and emphasized the need for integrated, technology-driven, and victim-centred approaches. Due to reliance on secondary data, causal claims are limited. It recommended strengthening international cooperation, enhancing institutional capacity, and addressing socio-economic vulnerabilities to effectively combat human trafficking. The research contributed to the broader understanding of transnational crime and provided practical implications for policymakers and practitioners. References Anguita-Olmedo, C. (2025). The convergence of trafficking and migrant smuggling in West Africa. Social Sciences, 14(8), 447. https://doi.org/10.3390/socsci14080447 Bamigbade, O., Sheppard, J., & Scanlon, M. (2024). Computer vision for multimedia geolocation in human trafficking investigation: A systematic review. arXiv. https://doi.org/10.48550/arXiv.2402.15448 Bosworth, M., Fili, A., & Pickering, S. (2023). Women in immigration detention: Human rights and victimization. Theoretical Criminology, 27(2), 234–252. https://doi.org/10.1177/13624806211056804 Broadhurst, R., Bouhours, B., & Keo, C. (2023). Cyber-enabled human trafficking: Trends and challenges. Trends in Organized Crime, 26(2), 210–229. https://doi.org/10.1007/s12117-022-09452-3 Cockbain, E., Bowers, K., & Dimitrova, G. (2023). Human trafficking for labour exploitation: The results of a two-phase systematic review. Crime, Law and Social Change, 79(1), 1–26. https://doi.org/10.1007/s10611-022-10035-8 Cohen, R., et al. (2023). Cybercrime and human trafficking nexus. Deviant Behavior. https://doi.org/10.1080/01639625.2025.2470402 Cooper, F. I., van Bemmel, S. R., van der Leun, J. P., & Kunst, M. J. J. (2024). Factors influencing criminal justice responses to trafficking. Crime, Law and Social Change, 82(3), 623–658. https://doi.org/10.1007/s10611-024-10161-x Demeke, M. A. (2024). Human trafficking and global governance challenges. Journal of Human Trafficking. https://doi.org/10.1080/23322705.2024.2300000 Dimas, G. L., Konrad, R. A., Maass, K. L., & Trapp, A. C. (2021). Operations research and analytics to combat human trafficking. arXiv. https://doi.org/10.48550/arXiv.2103.16476 Farrell, A., & de Vries, I. (2024). Measuring human trafficking: Challenges and progress. Annual Review of Criminology, 7, 291–313. https://doi.org/10.1146/annurev-criminol-032221-113213 Gallagher, A. T. (2023). The international law of human trafficking. Human Rights Quarterly, 45(2), 321–345. https://doi.org/10.1353/hrq.2023.0015 Giménez-Salinas, A. (2024). Female offenders in human trafficking. Social Sciences, 13(11), 605. https://doi.org/10.3390/socsci13110605 Healy, C. (2024). Victim protection frameworks in Europe. European Journal of Criminology. https://doi.org/10.1177/14773708241234567 Islam, F. (2023). Human trafficking law enforcement over victims and offenders: The perspective of anti-trafficking stakeholders. Victims & Offenders, 18(7), 1512–1540. https://doi.org/10.1080/15564886.2023.2227964 Karabatis, S. N., & Janeja, V. P. (2024). Creating geospatial trajectories from human trafficking corpora. arXiv. https://doi.org/10.48550/arXiv.2405.06130 Kaur, G., & Vageshjith, V. S. (2022). Human trafficking: A review. International Journal of Scientific Research in Computer Science Engineering and Information Technology, 8(3), 255–264. https://doi.org/10.32628/CSEIT228376 Khan, A., Iqbal, N., & Ahmad, I. (2022). Human trafficking in Pakistan: A qualitative analysis. Journal of Social Sciences Review, 2(3), 257–268. https://doi.org/10.54183/jssr.v2i3.136 L’Hoiry, X., Moretti, A., & Antonopoulos, G. A. (2024). Digital technologies and trafficking. Trends in Organized Crime. https://doi.org/10.1007/s12117-024-09526-4 Latonero, M. (2023). Technology and human trafficking. Journal of Human Trafficking, 9(3), 201–220. https://doi.org/10.1080/23322705.2023.2198765 Marek, M. (2024). Digital surveillance and transnational crime. Security Journal. https://doi.org/10.1057/s41284-024-00390-2 Musto, J., & Boyd, S. (2024). Anti-trafficking policies and criminal justice reforms. Criminology & Criminal Justice. https://doi.org/10.1177/17488958241234567 Okoye, U., & Vitela, M. (2023). Data challenges in human trafficking research. Journal of Crime and Justice, 46(4), 567–583. https://doi.org/10.1080/0735648X.2023.2187654 Oktavian, A. (2024). International law and human trafficking: Prevention and control in Indonesia. Russian Law Journal, 12(1). https://doi.org/10.2139/ssrn.XXXXXX Pajon, L., & Walsh, D. (2025). Investigating organised human trafficking crimes: Case studies of police investigations in England. Police Practice and Research. https://doi.org/10.1080/15614263.2024.2406841 Rafiq-uz-Zaman, M. (2025). The Integrated Skill-Based Education Framework (ISEF): An Empirically Grounded Model for Reforming Skill-Based Education in Pakistan. Global Social Sciences Review, X(III), 157-167. https://doi.org/10.31703/gssr.2025(X-III).14 Rafiq-uz-Zaman, M., Khalid, N., & Susanto, E. (2025). Addressing Environmental and Social Challenges: A Mixed-Method Study on the Education and Inclusion of Eunuchs in South Punjab, Pakistan. Social Science Review Archives, 3(1), 284-299. https://doi.org/10.70670/sra.v3i1.311 Reid, J. A., & Fox, B. (2023). Reforming the criminal justice response to human trafficking victims and offenders. Victims & Offenders, 18(3), 393–398. https://doi.org/10.1080/15564886.2023.2182856 Rivas, P., Cerny, T., Rodriguez, A., Turek, J., Giddens, L., Bichler, G., & Petter, S. (2024). Dataset challenges in analyzing trafficking risk. arXiv. https://doi.org/10.48550/arXiv.2405.13348 Rivas, P., et al. (2024). Challenges in datasets for analyzing trafficking risk. arXiv. https://doi.org/10.48550/arXiv.2405.13348 Sarkar, G., & Shukla, S. K. (2025). Cyber slavery infrastructures. arXiv. https://doi.org/10.48550/arXiv.2510.12814 Savona, E. U., & Riccardi, M. (2024). Data and policy in organized crime research. European Journal on Criminal Policy and Research. https://doi.org/10.1007/s10610-024-09567-1 Shafi, S., Akbar, W., & Rafiq-uz-Zaman, M. (2024). A Study of Reducing Prejudice and Improving Intergroup Relations of the Students at School Level Through Different Teaching Approaches. Global Social Sciences Review, IX(IV), 124-134. https://doi.org/10.31703/gssr.2024(IX-IV).13 Shelley, L. I. (2023). Human trafficking in the digital era. Journal of International Affairs, 76(2), 45–62. https://doi.org/10.2307/48687234 Sweileh, W. M. (2018). Research trends on human trafficking. Globalization and Health, 14, 106. https://doi.org/10.1186/s12992-018-0427-9 Totić, E. M. (2025). Activities of organized crime with a special focus on human trafficking. Science International Journal, 4(1), 147–153. https://doi.org/10.35120/sij.2025.4.1.147 van Rij, S. (2023). Organized crime networks and trafficking dynamics. Global Crime, 24(3), 289–310. https://doi.org/10.1080/17440572.2023.2204567 Vojta, F. (2024). The capacity of the International Criminal Court to fight human trafficking. Journal of Human Trafficking, 10(2), 391–402. https://doi.org/10.1080/23322705.2024.2303268 Winterdyk, J., & Jones, J. (2024). The Palgrave international handbook of human trafficking. Springer. https://doi.org/10.1007/978-3-319-63192-9 Zakir, M. H., Khan, S. H., Tayyab, A., & Ibrahim, S. (2024). The role of international law in addressing transnational organized crime. Journal of Asian Development Studies, 13(1), 283–294. https://doi.org/10.62345/jads.2024.13.1.24